2007
DOI: 10.17305/bjbms.2007.3021
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-Reactive Protein Concentration and Measures of Adiposity in Patients With Type 2 Diabetes Mellitus

Abstract: We investigated serum concentration of C-reactive protein (CRP) and measures of adiposity in 30 patients with type 2 diabetes mellitus (15 male, 15 female) and 30 age and sex-matched apparently healthy subjects. CRP concentration was determined by laser nephelometry (BN II Analyzer) and CardioPhase high-sensitivity CRP (DADE BEHRING) was used as reagent which consists of polystyrene particles coated with mouse monoclonal antibodies to CRP. Results have shown that serum CRP concentration in patients with type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“… 36 Previous studies have documented that obesity is associated with elevated levels of CRP. 37 39 In this study, in accordance with other researchers, 33 , 40 43 we observed a significant correlation between BMI and serum concentration of CRP in T2DM. It has been suggested that obesity and hyperglycemia induce oxidative stress, 44 46 which results in generation of free radicals in diabetic patients that could cause damage to the cell membrane and hence are associated with elevation of CRP, a mediator of inflammation.…”
Section: Discussionsupporting
confidence: 92%
“… 36 Previous studies have documented that obesity is associated with elevated levels of CRP. 37 39 In this study, in accordance with other researchers, 33 , 40 43 we observed a significant correlation between BMI and serum concentration of CRP in T2DM. It has been suggested that obesity and hyperglycemia induce oxidative stress, 44 46 which results in generation of free radicals in diabetic patients that could cause damage to the cell membrane and hence are associated with elevation of CRP, a mediator of inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…30 Zaciragic et al reported a direct relation between serum CRP concentrations and BMI in T2D. 31 The same relationship was documented by Rawson et al Other obesity markers such as total fat percentage were also investigated in the literature in relation to inflammation among patients with diabetes. 32 The findings of our study are in line with previously published work that showed an association between circulatory markers of chronic inflammation (CRP, IL-6) and body fat percentage.…”
Section: Discussionmentioning
confidence: 60%
“…These results were supported by findings from numerous studies that depicted a positive correlation between CRP and abdominal body fat. 31,33,36 Rexrode et al and Park et al also reported a very clear positive trend concerning CRP levels. 38,39 A study was conducted on elderly type 2 diabetic patients by Pedersen et al in 2003.…”
Section: Discussionmentioning
confidence: 85%
“…Obesity is a major risk factor, correlated with C-RP in populations with metabolic syndrome and/or T2D ( ADOPT ) [25,26]. Follow up studies in diabetic patients with coronary and carotid atherosclerosis, have shown that advanced atherosclerosis in T2D is connected with increased C-RP values and increased concentrations of advanced glycosylation products [27]. This high cardiovascular risk may be due to a combination of non-classical risk factors associated with insulin resistance, e.g.…”
Section: Discussionmentioning
confidence: 99%